2006
DOI: 10.2139/ssrn.878137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Causal Effect of Foreign Acquisition on Domestic Performances: The Case of Slovenian Manufacturing Firms

Abstract: Foreign direct investment is claimed to positively a¤ect …rms in the host country through a number of growth-enhancing e¤ects, generally termed "productivity spillovers." However, the empirical evidence for developing economies is quite controversial. This paper investigates the impact of foreign acquisition on the performances of a sample of Slovenian manufacturing …rms subject to takeover in 1997. The "propensity scorematching" estimation technique, also combined with the "di¤erence-in-di¤erences" approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, positive effects of cross border mergers and acquisitions have not been found in all contexts. Using a matched DiD on Slovenian manufacturing firms Salis (2006) finds no effect of foreign acquisitions on productivity, but rather that foreign firms tend to cherry pick the most productive firms.…”
Section: Introductionmentioning
confidence: 99%
“…However, positive effects of cross border mergers and acquisitions have not been found in all contexts. Using a matched DiD on Slovenian manufacturing firms Salis (2006) finds no effect of foreign acquisitions on productivity, but rather that foreign firms tend to cherry pick the most productive firms.…”
Section: Introductionmentioning
confidence: 99%
“…Although the influence of international acquisitions may follow in relation to the performance of local companies which were not the subject of acquisitions, belonging to the same or similar branch of the economy, this paper did not focus on the comparison with these companies, but only to compare performance before and after international acquisitions for the same company in order to confirm financial success. Among other things, a comparison with other local companies would have to include the assumption that the target company, as a subject of international acquisitions, was likely to be on a higher degree of efficiency in comparison to those that did not attract international acquisitions, as well as the theory reasonably believes (Salis, 2005). Other studies (Savovic, 2016) have also confirmed financial success of international acquisitions in the region of South Eastern Europe.…”
Section: Analysis Of Financial Changesmentioning
confidence: 99%